Pembuatan Profil Produk Untuk Pemasaran Barang Dan Jasa Bagi UP2K-PKK Kelurahan Prawirodirjan Gondomanan Yogyakarta - Harliyus Agustian; Asih Pujiastuti; Astika Ayuningtyas; Anton Setiawan Honggowibowo; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2019)
Family Income Improvement Company (UP2K) - Fostering Family Welfare (PKK) is a form of activity aimed at improving the family economy. The UP2K-PKK in Prawirodirjan brings together 27 players in the goods and services trade. It is possible to increase the marketing of UP2K-PKK participants' products in Prawirodirjan by creating product profiles as a means of offering or promoting. To create a product profile, you can create product photos using a smartphone. Taking pictures to take pictures of products requires photography and photo editing techniques using a smartphone. Improved photographic techniques and photo editing skills of UP2K-PKK participants can be achieved through training support provided by lecturers from the Computer Science Department of the Yogyakarta Adisucipto College of Technology as a form of community service activity.